THE ROLE OF CYANOBACTERIA IN CRYSTALLIZATION OF MAGNESIUM CALCITES - Zaitseva L.V.; Orleanskii V.K.; Gerasimenko L.M.; Ushatinskaya G.T. (My University, 2006)
Laboratory experiments showed the effect of the cyanobacterium Microcoleus chthonoplastes on the formation of magnesium calcites, using model solutions (2.14M MgCl2-0.05M CaCl2-0.6M NaCl-0.18M NaHCO3). The conditions of existence of cyanobacteria in such solutions in light or darkness significantly alter the structure of the sediment and the shape and size of the carbonate crystals. Cyanobacteria slow down crystallization due to the formation of exometabolites with a chelating effect, which leads to the precipitation of high-magnesium calcites. In the photosynthetic environment the presence of huntite (CaMg3(CO3) 4), possible forerunner of dolomite, is prominent. © Pleiades Publishing, Inc. 2006.
Keywords: CYANOBACTERIA; HIGH MAGNESIUM CALCITE; HUNTITE; PRECIPITATION